SHORT-TERM AND LONG-TERM OUTCOMES OF ENDOVASCULAR VERSUS SURGICAL PALLIATION PROCEDURES FOR PULMONARY ARTERY ATRESIA WITH INTACT VENTRICULAR SEPTUM - Imanov, E.E.; Ditkivskyy, I.O.; Plyska, O.I.; Mazur, O.A.; Sloboda, A.O.; Abdullayev, F.Z. (World of Medicine and Biology, 2025)
With the purpose to compare in-hospital and late outcomes of endovascular palliation, and surgical interventions in patients with pulmonary artery atresia 138 consecutive patients with the same pathology were analyzed since 2006 (115 patients underwent surgery – 160 surgical procedures, and 23 – underwent 32 endovascular procedures). Long-term outcomes studied on 12 years. The necessity for re-interventions following endovascular, and surgical procedures was analyzed. In surgical group mean length of hospital stay was 26±18.6 days, in endovascular group–22±5.7 days. Rate of surgical and endovascular procedures for pulmonary artery atresia Type I was 53.9 % and 56.5 %, respectively, whereas patients with pulmonary artery atresia Type II: 41.7 % vs.17.4 %, respectively (p
Keywords: pulmonary artery atresia; endovascular interventions; surgical procedures